The impact of breast cancer surgery on functional status in older women – A systematic review of the literature. Issue 8 (August 2021) - Harrison, C.A.; Parks, R.M.; Cheung, K.L.
Abstract: Primary endocrine therapy as treatment of breast cancer is only recommended in older women with limited life expectancy. However, many older women opt for endocrine therapy due to concerns regarding frailty and potential decline in function after surgery. A decline in functional status after surgery is documented in some cancer types, such as colorectal, however, the full impact of breast cancer surgery is less understood. A systematic review was performed to examine the evidence for impact of breast cancer surgery on functional status in older women. PubMed and Embase databases were searched. Studies were eligible if performed within the last 10 years; included patients over the age of 65 years undergoing breast cancer surgery; included stratification of results by age; measured functional status pre-operatively and at least six months following surgery. A total of 11 studies including 12 030 women were appraised. Two studies represented level-II and nine level-IV evidence. Overall, physical activity level was negatively impacted by breast cancer surgery and this was compounded by the extent of surgery. Evidence for impact of breast cancer surgery on quality of life, fatigue and cognition, was conflicting. The possibility of decline in functional status after breast cancer surgery should be discussed in all older women considering surgery. A structured exercise program may improve the negative effects of surgery on physical activity. Further work is required in the areas of quality of life, fatigability and cognition.